Effect of cigarette smoking on the specific antibody response in pigeon fanciers. Issue 10 (October 1988) - Anderson, K; Morrison, S M; Bourke, S; Boyd, G
Abstract : Titres of circulating IgG antibodies to pigeon gammaglobulin and end expired carbon monoxide concentrations were measured in 86 pigeon fanciers attending the "Show of the Year." Antibody levels were significantly higher in non-smokers and in those with end expired carbon monoxide concentrations below 10 parts per million.